Impacts of land use changes and land management practices on upland catchment sediment dynamics: Pontbren, mid-Wales - Henshaw, Alexander J. (2009)
There is growing concern that the adoption of intensive agricultural land management practices in upland areas of the UK over the past 50-60 years may have affected hydrological responses and sediment transfer regimes in river catchments and could, therefore, be contributing to increased levels of flood risk and ecological disturbance. However, recent evidence from a research catchment at Pontbren in mid-Wales indicates that the implementation of a more sustainable livestock farming strategy could help to mitigate some of these impacts, raising the possibility that strategic land use planning could be used as a cost-effective, multi-functional river management option. The impacts of historical land use changes and land management practices on contemporary sediment dynamics in the study area are explored in this thesis through a system approach which acknowledges the importance of interrelationships between hydrological and geomorphological processes. Results from hydrological experiments and modelling exercises are used to inform analyses of spatial and temporal variation in sediment production and transfer from a variety of potential sources. Grazed, agriculturally-improved pastures were found to supply fine material to stream channels via both surface runoff and field drains. In particular, drain-derived sediment is likely to represent an important component of the total fine sediment yield in subcatchments where agricultural intensification has been widespread. Agricultural drainage ditches were also found to act as sources of sediment in such areas, along with eroding channel banks. Sediment production from bank sources may relate to historical changes in peak flows caused by agricultural intensification. Stream sediment yields are strongly related to differences in sediment supply from the aforementioned sources and could therefore be reduced by limiting mobilisation at the point of origin within the landscape. In terms of channel-derived material, this could be achieved through peak flow reductions associated with woodland and hedgerow restoration.